2015
DOI: 10.1016/j.jmb.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Localization Study of Yeast Pex11 Identifies Peroxisome–Mitochondria Interactions through the ERMES Complex

Abstract: Pex11 is a peroxin that regulates the number of peroxisomes in eukaryotic cells. Recently, it was found that a mutation in one of the three mammalian paralogs, PEX11β, results in a neurological disorder. The molecular function of Pex11, however, is not known. Saccharomyces cerevisiae Pex11 has been shown to recruit to peroxisomes the mitochondrial fission machinery, thus enabling proliferation of peroxisomes. This process is essential for efficient fatty acid β-oxidation. In this study, we used high-content mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 57 publications
3
115
1
2
Order By: Relevance
“…In yeast, peroxisomes are major sites of fatty acid β-oxidation, the product of which, acetylcarnitine, can be used to make acetyl-CoA and power the TCA cycle and drive respiration. Two recent studies have found that peroxisomes are juxtaposed to ERMES marked ER-mitochondria contacts and the pyruvate decarboxylase complex in the mitochondrial matrix, which generates the hub metabolite, acetyl-CoA (Cohen et al, 2014; Mattiazzi Usaj et al, 2015). The connection between mitochondria and peroxisomes is mediated, in part, by interactions between the mitochondrial localized ERMES subunit, Mdm34 and Pex11, which has been implicated as a peroxisomal membrane shaping protein.…”
Section: Mitochondrial Membrane Contacts: a Mode Of Communication Formentioning
confidence: 99%
“…In yeast, peroxisomes are major sites of fatty acid β-oxidation, the product of which, acetylcarnitine, can be used to make acetyl-CoA and power the TCA cycle and drive respiration. Two recent studies have found that peroxisomes are juxtaposed to ERMES marked ER-mitochondria contacts and the pyruvate decarboxylase complex in the mitochondrial matrix, which generates the hub metabolite, acetyl-CoA (Cohen et al, 2014; Mattiazzi Usaj et al, 2015). The connection between mitochondria and peroxisomes is mediated, in part, by interactions between the mitochondrial localized ERMES subunit, Mdm34 and Pex11, which has been implicated as a peroxisomal membrane shaping protein.…”
Section: Mitochondrial Membrane Contacts: a Mode Of Communication Formentioning
confidence: 99%
“…Mdm10, Mdm12, and Mdm34 were required for proper localization of Pex11, whereas the absence of the ER-resident ERMES component, Mmm1, did not affect Pex11 localization. Pex11 was shown to physically interact with Mdm34 and was required for formation of contact sites between peroxisomes and mitochondria (101).…”
Section: Making Mitochondrial Membranes: the Contribution Of Er-mitocmentioning
confidence: 99%
“…However, how the regulation of peroxisomes is integrated with other organelles, especially the ER, is poorly understood. Further evidence of the intimate association between peroxisomes, the ER, and mitochondria comes from a recent systems biology screen in yeast that uncovered an association between the ER and mitochondrion encounter structure (ERMES) and peroxisomes [30]. Peroxisomes themselves are intimately associated physically with mitochondria [31,32] and can be formed from the ER [3335].…”
Section: Peroxisomes Are Not Autonomousmentioning
confidence: 99%